ANTI GASTRIC ULCER ACTIVITY OF LEAVES OF Pyracantha angustifolia (Franch.) C. K. Schneid IN RATS - Patricia, Randrianavony; Jedidia, Ranaovimanoelina Vonimboahirana; Nat, Quansah; Fanantenanirainy, Randimbivololona (European Scientific Journal, ESJ, 2015)
In vivo study to evaluate the anti-gastric ulcer activity of the hydro alcoholic extract of the leaves of Pyracantha angustifolia on rat has been conducted. Gastric ulcer was induced by the administration of indomethacin and absolute ethanol per os and pylorus ligation. The results obtained with the use of absolute ethanol showed that the extract protects gastric mucus. The extract, at a dose of 600mg/kg, reduced the ulcer index from 56.58% in the control group to 5.16% in the treated animals (p<0.05). The indomethacin provoked lesions of 11.36±0.08 mm2 in the control group and 1.21±0.12mm2 in the experimental group which received the 600mg/kg of the extract (p<0.05). After pylorus ligation, the pH of the gastric content of the control group animals was 2.13±0.21versus 3.89±0.49 for the animals which received 600mg/kg of the extract (p<0.05). These findings show that the extract of the leaves of Pyracantha angustifolia protects the gastric wall against the ethanol aggression, accelerates the healing of indomethacinprovoked gastric lesion and decreases gastric acidity after pylorus ligation.